Address pronouns in a diasystematic perspective - Jeppesen Kragh, Kirsten; Strudsholm, Erling (Scandinavian Studies in Language, 2023)
Our paper concerns different strategies of communication with respect to formality and politeness, and how these differences relate to the diasystematic dimensions. Our contrastive approach involves forms of address in French and Italian compared to Danish, German, and English norms and usage. Both Romance and Germanic languages have two systems of address pronouns with different levels of formality. There are, however, significant differences in usages in the respective languages, both typological and interlinguistic. Different language areas have different conventions for communication and politeness, and we believe that address forms reflect such socio-cultural differences. Our analyses of these differences are anchored in the diasystematic dimensions as proposed by Eugenio Coseriu, with special focus on the diaphasic variation and its intertwinement with diastratically conditioned factors.